Regenerative Medicine/Cardiac Cell Therapy: Pluripotent Stem Cells - Duran, Ana G.; Reidell, Olivia; Stachelscheid, Harald; Klose, Kristin; Gossen, Manfred; Falk, Volkmar; Röll, Wilhelm; Stamm, Christof (The Thoracic and Cardiovascular Surgeon, 2018)
For more than 20 years, tremendous efforts have been made to develop cell-based therapies for treatment of heart failure. However, the results of clinical trials using somatic, nonpluripotent stem or progenitor cells have been largely disappointing in both cardiology and cardiac surgery scenarios. Surgical groups were among the pioneers of experimental and clinical myocyte transplantation (“cellular cardiomyoplasty”), but little translational progress was made prior to the development of cellular reprogramming for creation of induced pluripotent stem cells (iPSC). Ever since, protocols have been developed which allow for the derivation of large numbers of autologous cardiomyocytes (CMs) from patient-specific iPSC, moving translational research closer toward clinical pilot trials. However, compared with somatic cell therapy, the technology required for safe and efficacious pluripotent stem cell (PSC)-based therapies is extremely complex and requires tremendous resources and close interactions between basic scientists and clinicians. This review summarizes PSC sources, strategies to derive CMs, current cardiac tissue engineering approaches, concerns regarding immunogenicity and cellular maturity, and highlights the contributions made by surgical groups.
Keywords: cell; biology; culture; experimental; stem cells; heart failure; tissue engineering